2010
DOI: 10.1517/17425247.2010.515584
|View full text |Cite
|
Sign up to set email alerts
|

Bicontinuous cubic liquid crystals as sustained delivery systems for peptides and proteins

Abstract: The bicontinuous cubic phase offers great potential in the field of peptide and protein delivery, but limited research in this area precludes definite conclusions to its future in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 75 publications
0
89
0
Order By: Relevance
“…It does not contain an ester functional group but consists of highly branched phytanyl tail with a tri-hydroxy headgroup. Both of DU and PT form cubic phases in presence of excess water which is also the case for the cores of stabilized lipid particles 13,45 ). 2.…”
Section: Preparation Of Lipid/water Bulk Phasesmentioning
confidence: 88%
See 2 more Smart Citations
“…It does not contain an ester functional group but consists of highly branched phytanyl tail with a tri-hydroxy headgroup. Both of DU and PT form cubic phases in presence of excess water which is also the case for the cores of stabilized lipid particles 13,45 ). 2.…”
Section: Preparation Of Lipid/water Bulk Phasesmentioning
confidence: 88%
“…The control over the particle size and biocompatibility is of utmost importance in order to optimize the therapeutic efficacy and hence the applicability of nanoparticles 7,8 . Lipids [9][10][11][12][13] , polymers 14,15 , metals 16,17 and carbon nanotubes 18,19 have been commonly employed as nanocarriers for various biomedical and pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Within the food and pharmaceutical research, LLC nano materials have shown potentials in the development of novel delivery systems. [4][5][6] These nanostructures are self-assemblies of naturally occurring surfactantlike lipid molecules which are closely related to those observed in biological membranes and empower the formation of efficient delivery matrices due to their impressive characteristics:…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Major application of internally self-assembled lipid particles is for 'drug delivery' because of the possibility of loading them with hydrophilic, hydrophobic and amphiphilic molecules. [31][32][33] In this work we exploit CNTs as novel stabilizers for nanostructured lipid particles as depicted in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%